Pneumatic Vitreolysis for the Treatment of Symptomatic Vitreomacular Traction: A Prospective Pilot Study. (September 2018) - Anderson, Matthew F.; Magal, Itay; Ells, Anna; Fielden, Michael; Williams, R. Geoff; Kherani, Amin
Purpose: The purpose of this study was to determine the efficacy of pneumatic vitreolysis in the treatment of symptomatic focal vitreomacular traction (VMT). Methods: Patients choosing intravitreal gas injection as their preferred treatment for symptomatic VMT were invited to participate in this prospective study; 0.3 mL of perfluoropropane gas was injected. Optical coherence tomography was performed pre-and postprocedure to determine the proportion of eyes showing release of VMT. Results: Nine eyes of nine participants were included in the study, with a mean follow-up of 5.0±1.8 months. Gas injection resulted in the release of VMT in 7 of 9 eyes (78%) during the course of the study. Both eyes in which the VMT failed to release also showed an improvement in central macular anatomy. Mean visual acuity improved from logarithm of the minimum angle of resolution (logMAR) 0.33±0.14 (Snellen equivalent, ∼20/42) to logMAR 0.24±0.21 (Snellen, ∼20/35) at final follow-up ( P = .03); 8 of 9 patients (89%) reported a subjective improvement in their presenting symptoms and/or vision during the study period. The mean maximum foveal thickness of 480 ± 22 μm at baseline reduced to 282 ± 94 μm by the time of the final visit ( P = .002). Two patients had retinopexy for retinal breaks/suspect breaks. Conclusions: Pneumatic vitreolysis is an effective treatment for symptomatic VMT and may offer cost savings for patients and/or health services.